2018
DOI: 10.1136/bmjsem-2018-000377
|View full text |Cite
|
Sign up to set email alerts
|

Fifth metatarsal stress fracture in elite male football players: an on-field analysis of plantar loading

Abstract: ObjectiveEvaluate plantar loading during ‘on-field’ common football movements in players after fifth metatarsal (MT-5) stress fracture and compare with matched healthy players.MethodsFourteen elite male soccer players participated in the study conducted on a natural grass playing surface using firm ground football boots. Seven players who had suffered a primary stress fracture (MT-5 group) and seven matched healthy players (controls, CON) performed three common football movements while in-shoe plantar loading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…The risk of this exact injury may be related to the profile of the player, the position on the field and the type of training adequate for his/her field position. It has been shown that midfielders are more likely to have their metatarsal bone damaged, and the presented outcomes on this issue are consistent with the literature data ( Thomson et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The risk of this exact injury may be related to the profile of the player, the position on the field and the type of training adequate for his/her field position. It has been shown that midfielders are more likely to have their metatarsal bone damaged, and the presented outcomes on this issue are consistent with the literature data ( Thomson et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…Exogen), which shortens the time of bone regeneration and remodeling ( Nolte et al, 2016 ; Teoh et al, 2018 ). Implementing early conditioning, gait re-education and subsequent running are possible due to an anti-gravity treadmill (Alter G), which is gaining more popularity in innovative rehabilitation protocols ( Thomson et al, 2018 ). During the last phase of rehabilitation and in the programming of sports training, the player's position on the pitch should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 The second is traction stress caused by the tension of the tissues attached to the proximal part of the fifth metatarsal bone during ankle plantarflexion. 38 The risk factors for bending stress have been reported to be an increase in anterior lateral plantar pressure, 1,11,35,40 hindfoot varus alignment, 20,29 forefoot supination alignment, 21 metatarsal adduction alignment, 15,43 reduced toe grip force, 10 hip internal rotation limitation, 31 and narrow shoe width. 16 However, risk factors for traction stress have not been fully elucidated, and it has been pointed out that traction stress may have an adverse effect on fracture incidence and healing.…”
mentioning
confidence: 99%